Causes and obstetric factors associated with timing of neonatal deaths in Soweto, South Africa - Admire Chikandiwa; Sana Mahtab; Firdose L. Nakwa; Nadia Umuneza; Vicky Baillie; Ziyaad Dangor; Sithembiso Velaphi; Yasmin Adam; Amy Wise (Reproductive, Female and Child Health, 2024)
Abstract Objective Describe characteristics of women whose decedents died during the neonatal period and explore factors associated with postnatal age at time of death. Methods Analysis of data collected at the Child Health and Mortality Prevention Surveillance (CHAMPS) South Africa study site. CHAMPS generates cause of death data in children across nine sites in low‐ and middle‐income countries. Postnatal age at time of neonatal death was evaluated by Kaplan–Meier methods. Factors associated with time to neonatal death were evaluated using Cox proportional hazards regression models. Analyses were conducted in Stata 15.0®. p < 0.05 was considered statistically significant. Results There were 225 neonatal deaths during the study period, of which 197 (87.5%) had data for mother‐neonate pairs, with 184 (81.7%) neonates having complete data. The median (IQR) maternal age at booking was 27 (23–34) years. Majority (72.3%, 142/197) of women were unmarried, unemployed (76.0%, 149/197) and were booked (85.0%, 141/166). There were 19.5% of women who had hypertensive disorders of pregnancy (HDP, 36/184) while 2.7% (5/184) had diabetes mellitus and 31.5% (58/184) were HIV positive. Most were early neonatal deaths (ENND; 79.4%, 146/184) and remainder (20.6%, 38/184) late neonatal deaths (LNND). The main underlying causes of death were prematurity (60.3%, 111/184), intrapartum hypoxia (17.4%, 32/184), neonatal sepsis (10.3%, 19/184) and congenital anomalies (9.2%, 17/184). Intrapartum hypoxia (Adjusted Hazard Ratio [aHR] = 2.01, 95% CI: 1.23–3.27, p = 0.01), assisted‐vaginal delivery compared to normal vaginal delivery (aHR = 1.96, 95% CI: 1.03–3.71, p = 0.04), preterm delivery (aHR = 1.62, 95% CI: 1.03–2, p = 0.04), Apgar score <7 at 5 min (aHR = 1.59, 95% CI: 1.01–2.31, p = 0.02) and a previous neonatal death ([aHR] = 1.33; 95% CI: 1.10–1.89, p = 0.04) were associated with earlier time to neonatal death. Conclusion Intrapartum complications were associated with earlier time to neonatal death. Improving intrapartum care can reduce neonatal deaths.